2021
DOI: 10.3390/ijms22031037
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Sex Pheromone Cyclo(l-Pro-l-Pro) of the Diatom Seminavis robusta towards a Chemical Probe

Abstract: As a major group of algae, diatoms are responsible for a substantial part of the primary production on the planet. Pennate diatoms have a predominantly benthic lifestyle and are the most species-rich diatom group, with members of the raphid clades being motile and generally having heterothallic sexual reproduction. It was recently shown that the model species Seminavis robusta uses multiple sexual cues during mating, including cyclo(l-Pro-l-Pro) as an attraction pheromone. Elaboration of the pheromone-detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In case of priming, the defense genes are faster or more strongly activated only when the plants are under attack ( De Kesel et al., 2021 ). Diproline is known to act as attraction pheromone for the diatom Seminavis robusta and has been detected in various other species ( Bonneure et al., 2021 ). Possibly, diproline-synthesizing species act as nutritional competitors for rice plants and therefore their presence needs to be detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of priming, the defense genes are faster or more strongly activated only when the plants are under attack ( De Kesel et al., 2021 ). Diproline is known to act as attraction pheromone for the diatom Seminavis robusta and has been detected in various other species ( Bonneure et al., 2021 ). Possibly, diproline-synthesizing species act as nutritional competitors for rice plants and therefore their presence needs to be detected.…”
Section: Discussionmentioning
confidence: 99%
“…The diketopiperazine diproline ( cyclo ( l -Pro- l -Pro)) is known to act as attraction pheromone for the diatom Seminavis robusta and has been detected in various other species, often as constituent of pheromonal secretions ( Bonneure et al., 2021 ). Recently, we demonstrated that foliar diproline treatment leads to systemic IR against Mg in rice grown under aerobic conditions ( De Kesel et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms, an important ecological group of phytoplankton, an extremely diverse group of microalgae, offer possibilities for biotechnological applications, e.g., sustainable pest control in agriculture [363,364]. The proline derived DKP, cyclo(L-Pro-L-Pro), has been recently reported as the first molecular structure of sex-inducing pheromone from marine diatom, Seminavis robusta sp., with moderate to good bioactivity, and low to no phytotoxicity [365].…”
Section: Pheromonal Scaffoldmentioning
confidence: 99%
“…All these features make CDPs an attractive choice as biocompatible, green, functionalizable, and cheap building blocks for smart materials with a wide scope of applications from industry to medicine. The basic design is very simple: two amino acids bound together in a cyclic structure with a defined stereochemistry (i.e., LL, LD/DL, or DD) and the possibility to further derivatize the side chains [ 42 , 43 , 44 , 45 , 46 ] of selected amino acids [ 47 , 48 , 49 , 50 ], as widely applied in nature [ 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%